BLOG WRITING AS A MEDIUM FOR ENGLISH SKILL DEVELOPMENT: IDENTIFYING GRAMMATICAL ERRORS AND LEXEME SELECTION - Mutiara Shal Sabillah; Evi Agustina Sari; Tiur Simanjuntak; Munaja Rahma; Moehamad Ridhwan (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
This study investigates blog writing as a dual-purpose medium for developing English language skills while serving as a promotional tool for Kopi 16Pro through the blog script titled